Pengembangan Budaya Sekolah di Madrasah Ibtidaiyah Negeri Buduran Sidoarjo - Moh. Haidar Abdillah (Universitas Muhammadiyah Sidoarjo, 2018)
Education is a conscious and systematic effort in developing the potential of students. Education is an effort of the community and the nation in preparing its young generation for the survival of a better society and nation in the future. Sustainability is marked by cultural inheritance and character that has been owned by the people and nation. This research is a type of qualitative research refers to a descriptive approach, while data collection techniques obtained through observation, interviews, and documentation will be analyzed through data reduction. The results of this study are MIN Buduran Sidoarjo has developed the school culture in familiarizing / applying behavior, traditions, student activities (Study of student leadership, Dhuha Prayers and Dzuhur congregation regularly, PHBI, PORSENI, art performances, etc.). Daily habits are of positive value and are characteristic, character or character, and the image of the school in MIN Buduran Sidoarjo. The conclusion of this study is that MIN Buduran has carried out the development of madrasah culture both in learning and positive daily habits, and is expected to teachers, parents, and students to be integrated into a tree in one that has a shared task and commitment to explore and nourish school culture. still exist and reach perfection. Madrasah culture will be fertile if parents are involved in supporting student activities.